THE EFFECT OF OUTDOOR LEARNING ACTIVITES ON STUDENTS' READING COMPREHENSION - Indah Miftah Awaliah (ELTIES : English Language Teaching for EFL Learners, 2019)
This research aimed to determine the influence of Outdoor Learning activities on the second year students’ reading comprehension especially in descriptive text. The study was quasi Experimental Design using “Nonequivalent Control Group Design. The study involved 40 students, second year students of English education department at UIN Alauddin Makassar. The independent variable of this research was Outdoor Learning Strategy and the dependent variable was students’ reading comprehension especially in descriptive text. In this research used instruments those were tests and questionnaire. The data were analyzed using descriptive statistic (frequency, mean score, and standard deviation) and inferential statistic (independent sample t-test). The research discovers that the reading comprehension of the second year students of English Education Department UIN Alauddin Makassar was not improved by using Outdoor Learning Activities. The result of the t-test also shown that the use of Outdoor Learning Activities in teaching reading especially in descriptive text was not effective in improving the students’ reading comprehension in descriptive text because the t-test, -0.39, was lower than t-table, 2.024 (-0.39 2.024).